Improving Students' Science Literacy through the Use of Phenomenon-Based Advance Organizer Chemistry Learning Tools in Petroleum Material - Azza Nuriah Widowati; Rudiana Agustini; Suyatno (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to examine the improvement in science literacy after learning using appropriate chemistry learning tools with a phenomenon-based Advance Organizer model on the subject of petroleum. This study assesses the improvement in science literacy through quantitative description. Data collection was conducted at Puri 1 Senior High School in Mojokerto through pretest and posttest using science literacy questions through trial I on 36 students in class XII-1 and trial II on two classes, XII-5 and XII-8, each with 36 students. The research results showed that the science literacy test scores achieved an n-gain score ranging from 0.76, categorized as high, indicating that this learning tool is effective. The science literacy indicators with high n-gain scores were explaining phenomena scientifically (0.77) and constructing and evaluating designs for scientific investigations, as well as critically interpreting scientific data and evidence (0.78). While the last indicator was in the moderate category with an N-gain score of 0.66, which is researching, evaluating, and using scientific information for decision-making and action, so it needs to be improved in the future.